Strengthening Hydromet and Early Warning Services in Belarus : A Road Map - World Bank (World Bank, Washington, DC, 2020)
The purpose of this road map is to assess the current capabilities of the Belarus hydrometeorological service to produce and deliver products and services based on the user needs. The analysis identifies gaps and challenges in producing and delivering fit-for-purpose weather, climate, hydrological, forest fire, and radiation-related information and services. The road map aims to provide the Government of the Republic of Belarus with a technical strategic framework to improve hydromet, forest fire, radiation monitoring and early warning services and systems, and the resulting socioeconomic benefits. The expectation is for Belarus to improve its capability and capacity to: (i) produce, manage, translate, and communicate hydromet, forest fire and radiation-related data and information, including forecasts and warnings for stakeholders and end-users; (ii) assist stakeholders and end-users in accessing, interpreting, and utilizing the generated data and information; (iii) improve the dissemination of and response to warnings for public safety and economic security; (iv) inform planning and decision-making for cost-effective investments in sustainable development and adaptation to climate change; and (v) make optimum use of all investments from the government and development partners. The road map lays out the current context of hydromet in Belarus, identifies the principal stakeholders and end-user community, and weighs these two factors against Belhydromet’s long-term strategy and the law of the Republic of Belarus. The road map drills down on the financial and technical infrastructure to determine if Belhydromet has the tools to match the country’s expectations and needs for services. The findings indicate: more robust tools can transform Belhydromet into a technically modern and sound hydromet service. The road map articulates three scenarios to transform Belhydromet to better deliver hydromet, forest fire and radiation-related information, and early warning services and systems.